A CACNA1C variant associated with reduced voltage-dependent inactivation, increased CaV1.2 channel window current, and arrhythmogenesis. - Jessica A Hennessey; Nicole J Boczek; Yong-Hui Jiang; Joelle D Miller; William Patrick; Ryan Pfeiffer; Brittan S Sutphin; David J Tester; Hector Barajas-Martinez; Michael J Ackerman; Charles Antzelevitch; Ronald Kanter; et al. (PLoS ONE, 2014)
Mutations in CACNA1C that increase current through the CaV1.2 L-type Ca2+ channel underlie rare forms of long QT syndrome (LQTS), and Timothy syndrome (TS). We identified a variant in CACNA1C in a male child of Filipino descent with arrhythmias and extracardiac features by candidate gene sequencing and performed functional expression studies to electrophysiologically characterize the effects of the variant on CaV1.2 channels. As a baby, the subject developed seizures and displayed developmental delays at 30 months of age. At age 5 years, he displayed a QTc of 520 ms and experienced recurrent VT. Physical exam at 17 years of age was notable for microcephaly, short stature, lower extremity weakness and atrophy with hyperreflexia, spastic diplegia, multiple dental caries and episodes of rhabdomyolysis. Candidate gene sequencing identified a G>C transversion at position 5731 of CACNA1C (rs374528680) predicting a glycine>arginine substitution at residue 1911 (p.G1911R) of CaV1.2. The allele frequency of this variant is 0.01 in Malays, but absent in 984 Caucasian alleles and in the 1000 genomes project. In electrophysiological analyses, the variant decreased voltage-dependent inactivation, thus causing a gain of function of CaV1.2. We also observed a negative shift of V1/2 of activation and positive shift of V1/2 of channel inactivation, resulting in an increase of the window current. Together, these suggest a gain-of-function effect on CaV1.2 and suggest increased susceptibility for arrhythmias in certain clinical settings. The p.G1911R variant was also identified in a case of sudden unexplained infant death (SUID), for which an increasing number of clinical observations have demonstrated can be associated with arrhythmogenic mutations in cardiac ion channels. In summary, the combined effects of the CACNA1C variant to diminish voltage-dependent inactivation of CaV1.2 and increase window current expand our appreciation of mechanisms by which a gain of function of CaV1.2 can contribute to QT prolongation.